Juridical Review of Online Fraud Convictions Against Job Vacancies - Safara, Intan (Politeknik Siber Cerdika Internasional, 2024)
This study discusses the comparison of the meaning of Indonesian Muslim tourists to the concept of Muslim-Friendly Tourism or PRM. This study aims to identify differences in the meaning and application of the concept of PRM between the two countries according to the perspective of Indonesian Muslim tourists. This research uses a qualitative approach with the research method used consisting of interviews and literature studies. The interviews were conducted with Indonesian Muslim tourists who had visited one or both of these countries. Literature studies are conducted as an additional source of information in researching related topics. The result of this study is that the UAE has been open to people from all over the world which resulted in several places providing non-halal food and drinks so that PRM in the UAE plays a role in facilitating the comfort of Muslim citizens and tourists. Japan has accommodated the various needs of Muslim tourists, although it is only found in a few big cities and some destination points visited by many Muslim tourists. Muslim travelers can understand this. Therefore, PRM is considered as a standardization of the needs of Muslim tourists that supports the comfort and safety of tourists, especially for Muslim tourists when traveling to the two countries.